Caveolin-1, a novel player in cognitive decline. (October 2021) - Tang, Wenxin; Li, Yansong; Li, Yan; Wang, Qiang
Highlights: Provide a comprehensive overview about how Caveolin-1 modulates pathogeneses of CD-associated diseases. Highlight the underlying mechanisms of Caveolin-1 to regulate brain development. Caveolin-1 represents a challenging but interesting therapeutic target for CD-related diseases. Abstract: Cognitive decline (CD), which related to vascular dementia, Alzheimer's disease, Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis and diabetes mellitus, is a growing health concern that has a great impact on the patients' quality of life. Although extensive efforts, the mechanisms of CD are still far from being clarified, not to mention the effective treatment and prevention strategies. Caveolin-1 (Cav-1), a trans-membrane protein, is a major component of the caveolae structure and scaffolding proteins. Recently, ample evidence depicts a strong correlation between Cav-1 and CD, however, the specific role of Cav-1 in CD has not been clearly examined and how they might be connected have yet to be identified. This review seeks to provide a comprehensive overview about how Cav-1 modulates pathogeneses of CD-associated diseases. In summary, Cav-1 can promote structural and functional plasticity of neurons, improve neurogenesis, relieve mitochondrial dysfunction, inhibit inflammation and suppress oxidative stress, which have shed light on the idea that Cav-1 may be an efficacious therapeutic target to treat CD.